2014
DOI: 10.1007/s13277-014-2251-z
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Prognostic value of CD133 expression in cancer patients treated with chemoradiotherapy: a meta-analysis

Abstract: Many studies evaluated the correlations of CD133 expression with the clinical outcomes in patients treated with chemoradiotherapy (CRT) but yielded controversial results. This meta-analysis was performed to identify the impacts of CD133 expression on the prognosis of cancer patients treated with CRT. Electronic databases updated up to March 2014 were searched to find relevant studies. Relevant literatures without any language restrictions were searched via electronic databases as follows: Web of Science (1945 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Previous studies have found that high CD133 expression is associated with decreased survival of patients with colorectal cancer and lung cancer [11,12]. Other studies found that CD133 expression may be positively correlated with poorer prognosis in cancer patients treated with chemoradiotherapy [43]. Thus, findings from previous studies suggest that CD133 expression has important roles in the progression of cancers.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have found that high CD133 expression is associated with decreased survival of patients with colorectal cancer and lung cancer [11,12]. Other studies found that CD133 expression may be positively correlated with poorer prognosis in cancer patients treated with chemoradiotherapy [43]. Thus, findings from previous studies suggest that CD133 expression has important roles in the progression of cancers.…”
Section: Discussionmentioning
confidence: 86%
“…CD133, one of the prognostic indicators for colorectal cancer, is a widely-applied tumor stem cell surface marker for colorectal cancer at present (Yao et al, 2014;Zheng et al, 2014). The studies found that the overall survival of patients with high expression of CD133 was markedly lower than those with low expression in the tumors, such as pancreatic cancer and lung cancer (Chen et al, 2014;Zhai et al, 2014;Tan et al, 2014). Wang et al studied the relationship between CD133 expression and prognosis in non-small cell lung cancer (NSCLC), and the results showed that CD133 was only related to tumor differentiated degrees and histological types instead of other clinicopathological features and diseasefree survival (Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A very recent meta-analysis carried out in 470 patients affected by different solid tumours treated with chemoradiotherapy assessed the prognostic impact of CD133 expression (28). The analysis pointed out that CD133 expression positively correlated with poorer progression-free and overall survival.…”
Section: Discussionmentioning
confidence: 99%